Cerebral Blood Flow of the Frontal Lobe in Untreated Children with Trigonocephaly versus Healthy Controls: An Arterial Spin Labeling Study - de Planque, Catherine A; Petr, Jan; Gaillard, Linda; Mutsaerts, Henk J M M; van Veelen, Marie-Lise C; Versnel, Sarah L; Dremmen, Marjolein H G; Mathijssen, Irene M J (Plastic and reconstructive surgery (1963), 2022)
Craniofacial surgery is the standard treatment for children with moderate to severe trigonocephaly. The added value of surgery to release restriction of the frontal lobes is unproven, however. In this study, the authors aim to address the hypothesis that the frontal lobe perfusion is not restricted in trigonocephaly patients by investigating cerebral blood flow. Between 2018 and 2020, trigonocephaly patients for whom a surgical correction was considered underwent magnetic resonance imaging brain studies with arterial spin labeling to measure cerebral perfusion. The mean value of cerebral blood flow in the frontal lobe was calculated for each subject and compared to that of healthy controls. Magnetic resonance imaging scans of 36 trigonocephaly patients (median age, 0.5 years; interquartile range, 0.3; 11 female patients) were included and compared to those of 16 controls (median age, 0.83 years; interquartile range, 0.56; 10 female patients). The mean cerebral blood flow values in the frontal lobe of the trigonocephaly patients (73.0 ml/100 g/min; SE, 2.97 ml/100 g/min) were not significantly different in comparison to control values (70.5 ml/100 g/min; SE, 4.45 ml/100 g/min; p = 0.65). The superior, middle, and inferior gyri of the frontal lobe showed no significant differences either. The authors' findings suggest that the frontal lobes of trigonocephaly patients aged less than 18 months have a normal cerebral blood flow before surgery. In addition to the very low prevalence of papilledema or impaired skull growth previously reported, this finding further supports the authors' hypothesis that craniofacial surgery for trigonocephaly is rarely indicated for signs of raised intracranial pressure or restricted perfusion for patients younger than 18 months. Risk, II.